DISTRIBUSI DAN POLA PERTUMBUHAN UDANG PUTIH Penaeus Merguiensis de Man DI PERAIRAN ESTUARI SUAKA MARGASATWA KARANG GADING SUMATERA UTARA - Audya Rahman; Miswar Budi Mulya; Yunasfi Yunasfi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
White shrimp Penaeus merguiensis de Man belonging to family of Penaeidae and the tribe of Decapoda. White shrimp are found in estuary waters of Karang Gading Wildlife North Sumatra. At the present, data about the presence of white shrimp in the waters of the estuary Wildlife Karang Gading North Sumatra have not been obtained, both of which include the abundance and growth patterns, so it is necessary to study. This study aims to determine the distribution and growth patterns of white shrimp in the waters of the estuary Wildlife Karang Gading North Sumatra. Sampling the white prawns done in May-June 2015 on estuary waters Karang Gading Wildlife North Sumatra use purse seine mini made of nylon material polifilamen, with a length of 10 m and a diameter of 3 m mouth opening. Sampling white shrimp is done every 21 days beginning at 08.00 am - 18.00 pm. At each sampling a one-time withdrawal mini purse seine along the 10 m at each station, so that the possibility of damage to the ecosystem of the study sites can be minimized. White shrimp were obtained at each station calculated the number of individuals, measured carapace length and body weight of shrimp, then performed the analysis includes the abundance, distribution, pattern of growth and condition factor. Measurement of physical-chemical parameters of water which include water temperature, water depth, water clarity, flow velocity, water pH, dissolved oxygen and salinity of water in the field at each station with three repetitions before sampling white shrimp. Especially for BOD5 and substrate fraction measurements performed in Agronomi laboratorium of Agriculture Faculty, North Sumatra University. The study concluded that the distribution of white shrimp in the waters of the estuary Wildlife Karang Gading belongs to the group distribution pattern. The growth pattern of white shrimp at stations 1 and 2 estuary waters of Karang Gading Wildlife Reserve is a positive allometric, while at station 3 is negative allometric. The condition factor of white shrimp in each station morphology have good plumpnessKey words:Distribution, estuary, growth pattern, white shrimp.